Einige kurze Bemerkungen zur Elision von “h” in der ägyptischen Sprache - Bojowald, Stefan.
This contribution investigates the elision of “h” in the Egyptian language. The topic has already been dealt with a few times in research. The present article adds four new examples to the list, all of which originate from the Middle Kingdom. By comparison with other hamito-semitic (afro-asiatic) languages, the phenomenon is put in a broader context.